Pengaturan Pemusnahan Barang Bukti Digital Berupa Akun Elektronik dalam Sistem Peradilan Pidana di Indonesia - Purnomo, Yogi; L., Sahuri; Siregar, Elizabeth (AL-SULTHANIYAH, 2026)
The development of information technology has introduced a new form of evidence in criminal proceedings, namely electronic accounts that serve as instruments, means, or proceeds of crime. However, Indonesia’s criminal justice system still lacks clear and comprehensive legal provisions regarding the destruction of electronic accounts as digital evidence. Existing regulations in the Criminal Procedure Code (KUHAP), the Electronic Information and Transactions Law (ITE Law), Government Regulation No. 71 of 2019, and other technical provisions have not explicitly defined the concept, authority, or procedure for such destruction. This regulatory gap creates legal uncertainty, inconsistent practices among law enforcement agencies, and potential violations of privacy rights. This study employs a normative juridical method with statutory, conceptual, and case approaches to analyze the adequacy and coherence of current regulations. The findings highlight the need for a reformulation of criminal law policy to establish a prudent, procedurally just, and forensically accountable mechanism for destroying electronic accounts while ensuring data protection and safeguarding citizens’ privacy rights in the digital era.